2018
DOI: 10.1007/s11910-018-0884-9
|View full text |Cite
|
Sign up to set email alerts
|

Graded Combined Aerobic Resistance Exercise (CARE) to Prevent or Treat the Persistent Post-concussion Syndrome

Abstract: The direct evidence shows that graded exercise assessments are safe, and that aerobic exercise interventions are associated with improvement of multiple symptoms and other benefits, including earlier return-to-sport. The indirect evidence supports this approach via studies that reveal the potential mechanisms, and show benefits for related presentations and individual symptoms, including headaches, neck pain, vestibular problems, sleep, stress, anxiety, and depression. We document the forms of exercise used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 97 publications
0
8
0
Order By: Relevance
“…Recent studies investigated physical (e.g. aerobic exercise; Sullivan, Hills, & Iverson, 2018) and cognitive (e.g. light cognitive activity; Reed et al, 2019) treatment strategies to aid recovery, but these methods do not directly target emotional and psychological symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies investigated physical (e.g. aerobic exercise; Sullivan, Hills, & Iverson, 2018) and cognitive (e.g. light cognitive activity; Reed et al, 2019) treatment strategies to aid recovery, but these methods do not directly target emotional and psychological symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Other reviews have been published previously on specific aspects of PCS. For example, recent reviews [ 75 , 76 , 77 ] focused on the effect of physical exercise in patients with persistent PCS and found that exercise significantly reduced the severity of PCS, the percentage of patients with PCS, and days off work, as compared to controls. Other recent reviews addressed issues such as interventions in sport-related concussion [ 17 , 78 ], reporting evidence in support of cervical rehabilitation, vestibulo-ocular rehabilitation, aerobic exercise, or rTMS [ 51 , 79 ], suggesting promising preliminary results for the treatment of post-concussive depression and headaches.…”
Section: Discussionmentioning
confidence: 99%
“…For example, SRC patients with higher SES might benefit from additional psychoeducation and psychological treatment, as those patients have a higher risk for emotional disruption after SRC. In addition, specific subgroups of patients with persistent SRC might benefit from other existing and emerging treatments for persisting symptoms (e.g., cognitive behavioral therapy, graded exercise and cervical manual therapy) [41][42][43][44]. Future studies may provide valuable information on the role of prevailing symptoms in the efficiency of targeted treatment options for patient subgroups.…”
Section: Discussionmentioning
confidence: 99%